The Jurisdiction and the Competence of the European Public Prosecutors’ Office and the Prosecutor´s Office of the Slovak Republic in Criminal Proceedings in light of the Case Law of the Constitutional Court of the Slovak Republic - Patrik Gábor (Slovak Yearbook of European Union Law, 2026)
This article examines the systematic definition of the competence and jurisdiction of the European Public Prosecutor's Office (EPPO) and the Prosecutor's Office of the Slovak Republic (Prosecutor's Office SR) in criminal proceedings, analysing their normative foundations, institutional definition, and competences. Attention is paid to the legal provisions that exclude the jurisdiction of Slovak prosecutors in matters falling under the EPPO, and thus also the absence of powers of the Prosecutor General of the Slovak Republic to intervene in these proceedings. The structure of the EPPO's competences reflects the principle of solidarity, which obliges Member States to contribute to the effective enforcement of Union law while respecting EPPO’s autonomy. The article is based on an analysis of the relevant provisions of the Criminal Code and the Regulation on the EPPO, as well as on scholarly articles and the Constitutional Court of the Slovak Republic´s case law. The aim of the contribution is to highlight the systemic and practical consequences of the EPPO’s autonomy, especially regarding the possibility of applying extraordinary remedies by both bodies, thereby providing an overview of the legal framework and contributing to a better understanding of the architecture of criminal proceedings in the European context.